Propulsion and braking mechanism of underwater undulatory swimming: an analysis of the fluid force of each vortex of the feet, trunk, and upper limbs - Tanaka, T.; Hashizume, S.; Kurihara, T.; Isaka, T. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
Swimmers generally use underwater undulatory swimming (UUS) during the start and turn phases of freestyle, backstroke, and butterfly events. Swimmers can produce greater horizontal body velocities during UUS than during surface swimming (Veiga and Roig, 2016). Moreover, swimmers have been suggested to propel underwater using UUS to improve their overall swimming race time (Veiga et al., 2014). Therefore, the investigation of the propulsion mechanisms during UUS is a popular topic in swimming research. Vortex generation around the feet, trunk, and arm of swimmers has been observed during UUS (von Loebbeck et al., 2009; Tanaka et al., 2022). Momentum changes in the water-flow field induce vortex generation (Matsuuchi et al., 2009). The propulsion or braking fluid force is generated by changes in the momentum of the flow field (Matsuuchi et al., 2009). Reciprocal acceleration and deceleration of the horizontal body velocity were observed during a one-kick cycle on the UUS (Atkison et al., 2014). A previous study suggested that the propulsion and braking fluid forces were produced by the vortices of the feet (von Loebbecke et al., 2009). A recent study indicated that vortices on the ventral side of the trunk are related to a high horizontal UUS velocity (Tanaka et al., 2022). These previous studies suggested that increasing and decreasing UUS velocities are associated with the vortices generated around the swimmers` whole body. This indicates that the propulsion and braking mechanisms of UUS can be revealed by analyzing vortex generation. Previous studies have suggested that all vortices generated by a swimmer`s whole body are associated with propulsion and braking during UUS (von Loebbeck et al., 2009; Tanaka et al., 2022). Moreover, a previous study determined the fluid force of vortices for dolphins using vortex circulation, segment velocity, and segment length (Fish et al., 2014). If we determine the fluid force of each vortex of the feet, trunk, and upper limbs for humans, the details of the propelling and braking mechanisms of UUS can be revealed; however, this has never been investigated. Therefore, this study aims to investigate the propulsion and braking mechanisms of UUS by determining the fluid force of the vortices of the feet, trunk, and upper limbs.